How VIRTUE-BOOK Improves Integrity and Recovers Learning Loss for Elementary School Students - Nanda Veruna Enun Kharisma; Hermanto Hermanto (STAI Hubbulwathan Duri, 2023)
Digital-based learning media plays a vital role in improving the quality of student character and post-COVID-19 learning. This research aimed to explain how VIRTUE-BOOK improves integrity and recovers learning loss for elementary school students. This research is a research and development (RD) with the ADDIE model. This research focuses on the implementation (I) and evaluation (E) stages. The research was carried out from August to September 2022. Implementation was carried out through a quasi-experiment with the subject of 3rd-grade elementary school students. There were 15 students for each of the experimental and control classes. Data collection used questionnaires (scales) and tests. Data analysis was performed by calculating the percentage of increasing the integrity index and decreasing learning loss, then calculating its effectiveness using MANOVA with a significance level of 5% (0,05); N-Gain test; and effect size test. The results of this research indicate that the digital fairytale book